PERANAN PEMBELAJARAN ORGANISASIONAL DALAM MENGKONVERSIKAN ORIENTASI PASAR MENJADI KINERJA PEMASARAN : PROSES DAN AGENDA PENELITIAN - Suliyanto Suliyanto (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2010)
Many studies have proved that market orientation has an influence on marketing performance,but it is considered a market orientation is not sufficient to improve marketing performance.Market orientation will be able to improve marketing performance when combined with organizationallearning, but the role of organizational learning in the convert market orientationinto marketing performance is unclear. By integrating variables of organizational learning asa single entity-market orientation-organizational learning- innovation, competitive advantagemarketing performance in a study as one is expected to clarify the role of learning in the convertmarket orientation into marketing performance has been deemed not clear.Keyword: Organizational Learning, Market Orientation, Competitive Advantage and Marketing Performance